2015
DOI: 10.1371/journal.pone.0120390
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Dicer Protein by I7 Protease during Vaccinia Virus Infection

Abstract: Dicer is the key component in the miRNA pathway. Degradation of Dicer protein is facilitated during vaccinia virus (VV) infection. A C-terminal cleaved product of Dicer protein was detected in the presence of MG132 during VV infection. Thus, it is possible that Dicer protein is cleaved by a viral protease followed by proteasome degradation of the cleaved product. There is a potential I7 protease cleavage site in the C-terminus of Dicer protein. Indeed, reduction of Dicer protein was detected when Dicer was co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…It is possible that specificity in this regard simply relates to endogenous miRNA properties in the cell but given that some miRNAs can be advantageous to viruses [ 48 ] while others broadly antiviral [ 49 ], it is hard to imagine the virus would not evolve to elicit more control over these molecules. At the same time additional reports have demonstrated that VACV also encodes mechanisms for inhibiting pre-miRNA processing [ 12 , 50 ] which could also contribute to the increase in pre-miRNA forms and reduction of mature miRNAs at late time points that we also observe. In summary this virus interfaces with host small RNA biogenesis and turn over through multiple mechanisms and the functional consequences of this merit further attention.…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that specificity in this regard simply relates to endogenous miRNA properties in the cell but given that some miRNAs can be advantageous to viruses [ 48 ] while others broadly antiviral [ 49 ], it is hard to imagine the virus would not evolve to elicit more control over these molecules. At the same time additional reports have demonstrated that VACV also encodes mechanisms for inhibiting pre-miRNA processing [ 12 , 50 ] which could also contribute to the increase in pre-miRNA forms and reduction of mature miRNAs at late time points that we also observe. In summary this virus interfaces with host small RNA biogenesis and turn over through multiple mechanisms and the functional consequences of this merit further attention.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to CoVs, many other virus-encoded proteases are reported to target host proteins. For example, vaccinia virus-encoded I7 protease cleaves Dicer protein to suppress microRNA (miRNA) processing (72). The leader protease of foot-and-mouth disease virus (FMDV) cleaves RNA helicase LGP2 to mediate immune evasion (73).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid construction and DNA transfection. The expression plasmids used in this study were constructed using standard protocols as described in our previous studies (37). The primer sequences used for cloning are available upon request.…”
Section: Methodsmentioning
confidence: 99%